A Study on Student Attendance Analysis and Statistics Platform Based on Capture Recognition Technology - Qianchuan Ding , Qun Yin , Pengfei Duan, Xianyun Zhang, Meisu Yin (Forest Chemicals Review, 1970)
With the development of face recognition technology and HD camera, it is possible to use face recognition to realize the classroom attendance statistics. The traditional way of classroom attendance statics needs teachers to roll call according to the list of students, but face recognition can not only save the time of class, but also lighten the burden of statistics attendance of school. This paper realizes the face recognition system of attendance analysis and statistics platform, and it needs cameras and a main computer. In software, under the development environment of VS2017, it relies on OPENCV, arcsoft face recognition SDK and My -SQL database realizes a real-time video stream face recognition system with C++ programming. The system captures the student face by the camera installed in the classroom, then using SDK extracts the face feature and compares with the feature in the database. When the compare value is over the set value, the system will output the corresponding students' information and completion time to the TXT file.